Double compensation temperature regulating fiber with skin-core structure and preparation method thereof
By adopting double-compensated temperature-regulating fibers with a leather core structure in the fibers, combining photoresponsive polymers and phase-change heat storage materials, the problem of difficulty in combining photoresponsive components and phase-change heat storage components in the prior art is solved, efficient photothermal conversion and reversible phase-change heat storage, and the warmth and heat storage properties of the fibers are improved.
Patent Information
- Application Number
- CN202311072658.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-08-24
AI Technical Summary
In the prior art, the photoresponsive component and the phase change heat storage component are difficult to effectively combine, resulting in insufficient warmth and heat storage properties of the fibers in cold environments.
The double-compensated temperature-regulating fiber with a leather core structure is a photoresponsive polymer/high-entropy carbon-based composite material, and the core layer is a phase-change heat storage material with a composite structure. The photothermal conversion and reversible phase-change heat storage are achieved through uniform embedding of high-entropy carbon-based nanoparticles and high-entropy vanadium-based shell phase-change nano-microcapsules.
The fiber has high-efficiency photothermal conversion and reversible phase change heat storage, which improves the warmth and heat storage properties, and has excellent cyclability. The phase change enthalpy value retention rate is >95% after 1,000 heating and cooling cycles.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, in particular to a double-compensation temperature-regulating fiber with a sheath-core structure and a preparation method thereof. Background Art
[0002] With the increase in extreme weather and the improvement of people's living standards, people's requirements for winter warm clothing have gradually shifted from low price and warmth to warmth, comfort, and lightness. Therefore, the development of functional synthetic fiber materials to achieve efficient warmth and heat storage functions has become a research focus in recent years.
[0003] The method of converting light energy into heat energy through photoresponsive technology, and then storing heat energy through phase change materials and releasing it in a cold environment can effectively improve the warmth retention and heat storage of winter warm clothing. However, most of the current materials have a single photoresponsive function or heat storage function, so the development of composite materials of photoresponsive materials and phase change materials is the focus of the development of functional thermal insulation materials. At present, there is a related study (CN115341302A) that combines the two, but the aerogel used in its photoresponsive component has a large particle size and poor thermal conductivity, which not only makes the fiber strength poor, but also increases the phase change hysteresis of the phase change component. In addition, the PEG-PET copolymer solid-solid phase change material used in its phase change component has a phase change temperature of >100°C, and the phase change temperature cannot be reached during actual use, and thus has no heat storage function.
[0004] Therefore, there is an urgent need to develop high-performance photoresponsive materials and recyclable phase change materials, and their organic combination is a difficulty in the development of functional thermal insulation materials. Summary of the invention
[0005] The purpose of the present invention is to solve the above problems and provide a double compensation temperature regulating fiber with a skin-core structure and a preparation method thereof, so as to solve the difficult problem of effectively combining light response components and phase change heat storage components in high-efficiency warm and heat storage clothing.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] The present invention provides a double compensation type temperature regulating fiber with a skin-core structure, wherein the temperature regulating fiber comprises a skin layer and a core layer;
[0008] The skin layer is a photoresponsive polymer / high entropy carbon-based composite material, and the skin layer is used for photothermal conversion;
[0009] The core layer is a phase-change heat storage material of a composite structure, and the core layer is used for reversible phase-change heat storage;
[0010] The cortex includes a polymer matrix and high-entropy carbon-based nanoparticles, wherein the high-entropy carbon-based nanoparticles are uniformly embedded in the polymer fibers, wherein the polymer content accounts for 85-95wt% and the high-entropy carbon-based nanoparticles account for 5-15wt%;
[0011] The core layer includes a polymer matrix and high entropy vanadium-based shell phase-change nano-microcapsules, and the nano-microcapsules are uniformly embedded in the polymer fibers, wherein the polymer content accounts for 85-95wt% and the high entropy vanadium-based shell phase-change nano-microcapsules account for 5-15wt%.
[0012] Furthermore, in the cortex:
[0013] The polymer matrix includes one or more of polyester, polyamide, polyethylene, polypropylene, polylactic acid, and polyimide;
[0014] The high entropy carbon-based nanoparticles include one or more of (Ti,Hf,Nb,Tl)ZrC, (Ti,Hf,V,Tl)ZrC, (Ti,Hf,V,Nb)ZrC, (Ti,Hf,V,W)ZrC, and (Ti,Hf,Nb,W)ZrC.
[0015] Furthermore, in the core layer:
[0016] The polymer includes one or more of polyester, polyamide, polyethylene, polypropylene, polylactic acid, and polyimide;
[0017] The high entropy vanadium-based shell phase-change nano-microcapsules are composite materials with a core-shell structure;
[0018] The core layer of the high entropy vanadium-based shell phase change nanocapsules is a long carbon chain aliphatic hydrocarbon phase change material, including one or more of n-octadecane, n-nonadecane, n-eicosane and n-heneicosane, with a mass ratio of 30-90wt%.
[0019] The shell of the high entropy vanadium-based shell phase change nano-microcapsule is a high entropy vanadium-based phase change material X a V b O c , wherein X is selected from four or more of Ti, Hf, Nb, Tl, Zr, and W, a is the comprehensive stoichiometric number of all elements in X, a=b, a+b=c, and the mass proportion is 10~70wt%.
[0020] Furthermore, the double compensation temperature regulating fiber has a fineness of 30-300 dtex, a strength of >2.0 cN / dtex, a photothermal conversion efficiency of ≥2%, a phase change temperature of 20-50°C, a phase change enthalpy value of >15 J / g, and a phase change enthalpy value retention rate of >95% after 1000 heating and cooling cycles.
[0021] The second aspect of the present invention provides a method for preparing the double compensation temperature regulating fiber with the skin-core structure as described above, comprising the following steps:
[0022] S1: adding zirconium source, four or more inorganic precursors of Ti, Hf, Nb, Tl, Zr, W and chelating ligands to a compound solvent and uniformly mixing them, and vacuuming them under high humidity and negative pressure under stirring to obtain zirconium-based inorganic gel, and then ball milling to achieve atomic-level uniform distribution of inorganic elements to obtain uniform gel;
[0023] S2: drying the uniform gel obtained in S1, and calcining it in stages under a protective gas atmosphere to obtain a single crystal high entropy carbon-based powder, and then ball milling it to obtain high entropy carbon-based nanoparticles;
[0024] S3: adding the high entropy carbon-based nanoparticles obtained in S2 and the polymer masterbatch into a twin-screw extruder according to a preset mass ratio, and obtaining a uniformly mixed polymer / high entropy carbon-based composite masterbatch through high-temperature melting, extrusion molding and pelletizing processes;
[0025] S4: After the polymer / high entropy carbon-based composite masterbatch and high entropy vanadium-based shell phase change nano-microcapsule composite masterbatch obtained in S3 are fully dried, they are added into two sets of feed funnels of a high-speed melt spinning machine for spinning and drawing respectively, and a spinneret assembly with a skin-core structure is used in conjunction to obtain a skin-core structured double compensation type temperature regulating fiber.
[0026] Further, in S4, the preparation process of the high entropy vanadium-based shell phase change nano-microcapsule composite masterbatch comprises:
[0027] T1: Add polysorbate 80 to deionized water and stir thoroughly to mix evenly, melt Na2HPO4·12H2O and mix evenly with the dispersion, and obtain the aqueous phase after magnetic stirring;
[0028] T2: Add long carbon chain alkane into a reaction vessel, add sorbitan oleate and stir thoroughly to obtain an oil phase;
[0029] T3: adding the water phase obtained in T1 into the reaction vessel containing the oil phase in T2, heating in a water bath environment and stirring thoroughly to obtain a uniformly dispersed water-in-oil emulsion;
[0030] T4: The vanadium source and four inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W are weighed in molar ratio and added into a mixed solvent for stirring, followed by ball milling to achieve uniform distribution at the atomic level;
[0031] T5: slowly adding the mixed inorganic source obtained in T4 into the reaction vessel containing the water-in-oil emulsion in T3, adding the chelating ligand, and performing high-humidity negative pressure suction to further hydrolyze and condense the inorganic source, forming a high-entropy vanadium-based shell at the interface of the long carbon chain alkane and fully wrapping the core body;
[0032] T6: washing the core-shell nano-microcapsules obtained in T5 with a mixed solution of ethanol and water, and fully drying to obtain high entropy vanadium-based shell phase change nano-microcapsules;
[0033] T7: The high entropy vanadium-based shell phase change nano-microcapsules and polymer masterbatch obtained in T6 are added into a twin-screw extruder according to a preset mass ratio, and high entropy vanadium-based shell phase change nano-microcapsule composite masterbatch is obtained through high-temperature melting, extrusion molding and pelletizing processes.
[0034] Furthermore, in S1:
[0035] The molar ratio of the zirconium source to four inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W is 1:0.25:0.25:0.25:0.25, and the molar ratio of the zirconium source to the chelating ligand is 1:0.01-0.05;
[0036] The chelating ligand is acetic acid;
[0037] The high humidity negative pressure suction environment humidity is 85-99%, the negative pressure is 0.5-5MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol;
[0038] The ball mill is a zirconium ball dry mill with a rotation speed of 200 to 500 rpm and a time of 0.5 to 3 hours;
[0039] In S2:
[0040] The protective gas is high-purity nitrogen, the heating rate in the front section is controlled at 2~5℃ / min, the heating rate in the back section is controlled at 10~20℃ / min, and the holding time is 5~30min;
[0041] The ball mill is zirconium ball dry milling, the rotation speed is 300-500 rpm, and the time is 3-8 hours;
[0042] In S3:
[0043] The melting temperature of the twin-screw extruder is 180-320° C. The extruded nascent fibers are solidified in a water bath and pelletized by a pelletizer.
[0044] Further, in T1, the mass ratio of the polysorbate 80, deionized water and Na2HPO4·12H2O melt is 0.1:5:20, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes;
[0045] In T2, the mass ratio of the long carbon chain alkane to sorbitan oleate is 30-40:1, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes;
[0046] In T3, the water bath temperature is 50-70°C, the stirring speed is 200-500 rpm, and the time is 0.5-3 h;
[0047] In T4, the molar ratio of the vanadium source to the four inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W is 1:0.25:0.25:0.25:0.25, and the ball mill is zirconium ball dry milling, with a rotation speed of 300-500 rpm and a time of 1-5 hours;
[0048] In T5, the molar ratio of the vanadium source to the chelating ligand is 1:0.01-0.05;
[0049] In T5, the chelating ligand is acetic acid;
[0050] In T5, the environmental humidity of the high-humidity negative pressure suction is 85~99%, the negative pressure is 0.5~5MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol.
[0051] Further, in T6, the washing liquid used is a mixed liquid of 50% deionized water and 50% ethanol, the washing times are 3 to 5 times, and after washing, the washing is centrifuged at a speed of 3000 to 6000 rpm for 10 to 20 minutes, and the drying temperature is 40 to 60°C for 0.5 to 3 hours;
[0052] In T7, the melting temperature of the twin-screw extruder is 180-320° C., the screw speed is 5-50 m / min, the extruded nascent fibers are solidified in a water bath, and the pelletizer speed matches the screw speed.
[0053] Further, in S4, the drying condition is a gradient temperature increase, the first stage of temperature increase is from room temperature to 80°C over 30 minutes, the second stage of temperature increase is from 80°C to 100-120°C over 30 minutes, and the third stage of temperature increase is from 120-150°C over 1 hour;
[0054] In S4, the polymer / high entropy carbon-based composite masterbatch is loaded into the screw device A and passed into the cortex of the spinning assembly, and the high entropy vanadium-based shell phase change microcapsule composite masterbatch is loaded into the screw device B and passed into the core layer of the spinning assembly. The spinning process has a temperature of 180°C to 320°C, a spinning speed of 500 to 4500 m / min, and a drafting multiple of 1 to 4 times.
[0055] Compared with the prior art, the present invention has the following technical advantages:
[0056] The dual compensation thermostatic fiber of the present invention has excellent cyclable light response performance and heat storage performance, and can realize light heat and heat storage in a single fiber. The composite fiber fineness is 30-300 dtex, the strength is >2.3 cN / dtex, the phase change temperature is 20-50°C, the phase change enthalpy value is >15 J / g, there is no obvious phase change hysteresis phenomenon, the fiber shape is stable during the phase change process, there is no liquid leakage, and it has excellent cyclability. After 1000 heating and cooling cycles, the phase change enthalpy value retention rate is >95%. DETAILED DESCRIPTION
[0057] The dual compensation thermostatic fiber with a skin-core structure in the present invention comprises a skin layer and a core layer, wherein the skin layer is a photoresponsive polymer / high entropy carbon-based composite material, and the core layer is a phase change thermal storage material with a composite structure. The skin layer can realize efficient light-to-heat conversion, and the core layer can realize reversible phase change thermal storage.
[0058] The cortex includes a polymer matrix and high-entropy carbon-based nanoparticles, and the high-entropy carbon-based nanoparticles are uniformly embedded in the polymer fibers, wherein the polymer content accounts for 85-95wt% and the high-entropy carbon-based nanoparticles account for 5-15wt%; the polymer includes but is not limited to one or more of polyester, polyamide, polyethylene, polypropylene, polylactic acid, and polyimide, and the high-entropy carbon-based nanoparticles include but are not limited to one or more of (Ti, Hf, Nb, Tl)ZrC, (Ti, Hf, V, Tl)ZrC, (Ti, Hf, V, Nb)ZrC, (Ti, Hf, V, W)ZrC, and (Ti, Hf, Nb, W)ZrC.
[0059] The core layer includes a polymer matrix and a high-entropy vanadium-based shell phase-change nano-microcapsule, and the nano-microcapsule is uniformly embedded in the polymer fiber, wherein the polymer content accounts for 85-95wt%, and the high-entropy vanadium-based shell phase-change nano-microcapsule accounts for 5-15wt%; the polymer is not limited to one or more of polyester, polyamide, polyethylene, polypropylene, polylactic acid, and polyimide, and the high-entropy vanadium-based shell phase-change nano-microcapsule is a composite material of a core-shell structure. The core layer of the high-entropy vanadium-based shell phase-change nano-microcapsule is a long carbon chain aliphatic hydrocarbon phase change material, including but not limited to one or more of n-octadecane, n-nonadecane, n-eicosane, and n-heneicosane, with a mass ratio of 30-90wt%; the shell layer is a high-entropy vanadium-based phase change material X a V b O c , wherein X is four or more of Ti, Hf, Nb, Tl, Zr, and W, a is the comprehensive stoichiometric number of all elements in X, a=b, a+b=c, and the mass proportion is 10~70wt%.
[0060] The composite fiber has a fineness of 30~300dtex, a strength of >2.0cN / dtex, a photothermal conversion efficiency of ≥2%, a phase change temperature of 20~50℃, a phase change enthalpy value of >15J / g, no obvious phase change hysteresis, a stable fiber shape during the phase change process, no liquid leakage, and excellent recyclability. After 1000 cycles of heating and cooling, the phase change enthalpy value retention rate is >95%.
[0061] Double compensation temperature regulating fiber with skin-core structure and preparation method thereof, the method comprising the following steps:
[0062] Adding a zirconium source, four or more inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W, and a chelating ligand into a compound solvent and uniformly mixing them;
[0063] The uniform sol obtained in 1) is subjected to high-humidity negative pressure suction under stirring to obtain a zirconium-based inorganic gel;
[0064] 2) subjecting the obtained gel to high-energy ball milling to achieve atomic-level uniform distribution of inorganic elements;
[0065] After the uniform gel obtained in 3) is fully dried, it is calcined in stages under a protective gas atmosphere, first slowly heating to 800°C and keeping the temperature for 2 hours to remove the organic side groups of the colloid, and then rapidly heating to 1500-2000°C to achieve rapid carbonization;
[0066] The single crystal high entropy carbon-based powder obtained in 4) is subjected to secondary high-energy ball milling to rapidly crush it into nano-scale particles;
[0067] The high entropy carbon-based nanoparticles and polymer masterbatch obtained in 5) are added into a twin-screw extruder according to a mass ratio, and a uniformly mixed polymer / high entropy carbon-based composite masterbatch is obtained through high-temperature melting, extrusion molding and pelletizing processes;
[0068] Polysorbate 80 was added into deionized water and stirred thoroughly and mixed evenly, Na2HPO4·12H2O was melted and mixed evenly with the dispersion, and the aqueous phase was obtained after magnetic stirring;
[0069] Add long carbon chain alkane into a three-necked flask, add sorbitan oleate and stir thoroughly to obtain an oil phase;
[0070] Add the water phase obtained in 8) into the three-necked flask containing the oil phase, heat in a water bath and stir thoroughly to obtain a uniformly dispersed water-in-oil emulsion;
[0071] The vanadium source and four inorganic precursors of Ti, Hf, Nb, Tl, Zr and W are weighed in molar ratio and added into a mixed solvent for stirring, followed by high-energy ball milling to achieve uniform distribution at the atomic level;
[0072] The mixed inorganic source obtained in 10) is slowly added into a three-necked flask containing the water-in-oil emulsion, a chelating ligand is added, and high-humidity negative pressure suction is performed to further hydrolyze and condense the inorganic source, forming a high-entropy vanadium-based shell at the interface of the long carbon chain alkane and fully wrapping the core body;
[0073] The core-shell nanocapsules obtained in 11) were washed with 50% ethanol and fully dried to obtain high entropy vanadium-based shell phase change nanocapsules.
[0074] The high entropy vanadium-based shell phase change nano-microcapsules obtained in 12) and the polymer masterbatch are added into a twin-screw extruder according to a mass ratio, and a uniformly mixed composite masterbatch is obtained through high-temperature melting, extrusion molding and pelletizing processes;
[0075] The polymer / high entropy carbon-based composite masterbatch obtained in 6) and the high entropy vanadium-based shell phase change nano-microcapsule composite masterbatch obtained in 13) are fully dried and added into two sets of feed funnels of a high-speed melt spinning machine for spinning and drawing, and a spinneret assembly with a skin-core structure is used in conjunction to obtain a skin-core structured double-compensation temperature-regulating fiber.
[0076] In step 1), the molar ratio of the zirconium source to the inorganic precursors of four kinds of Ti, Hf, Nb, Tl, Zr, and W and the chelating ligand is 1:0.25:0.25:0.25:0.25, and the molar ratio of the zirconium source to the chelating ligand is 1:0.01-0.05.
[0077] In step 2), the environmental humidity of the high-humidity negative pressure suction is 85-99%, the negative pressure is 0.5-5 MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol.
[0078] In step 3), the ball milling is zirconium ball dry milling, the rotation speed is 200-500 rpm, and the time is 0.5-3 hours.
[0079] In step 4), the protective gas is high-purity nitrogen, the heating rate of the front section is controlled at 2-5°C / min, the heating rate of the rear section is controlled at 10-20°C / min, and the insulation time is 5-30min.
[0080] In step 5), the ball milling is zirconium ball dry milling, the rotation speed is 300-500 rpm, and the time is 3-8 hours.
[0081] In step 6), the melt temperature of the twin-screw extruder is 180-320° C., the screw speed is 5-50 m / min, the extruded nascent fibers are solidified in a water bath, and the pelletizer speed matches the screw speed.
[0082] In step 7), the mass ratio of polysorbate 80, deionized water and Na2HPO4·12H2O melt is 0.1:5:20, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes.
[0083] In step 8), the mass ratio of the long carbon chain alkane to sorbitan oleate is 30-40:1, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes.
[0084] In step 9), the water bath temperature is 50-70° C., the stirring speed is 200-500 rpm, and the stirring time is 0.5-3 hours.
[0085] In step 10), the molar ratio of the vanadium source to the inorganic precursors and chelating ligands of four kinds of Ti, Hf, Nb, Tl, Zr, and W is 1:0.25:0.25:0.25:0.25, and the ball mill is zirconium ball dry milling with a rotation speed of 300-500 rpm and a time of 1-5 hours.
[0086] In step 11), the molar ratio of the vanadium source to the chelating ligand is 1:0.01-0.05.
[0087] In step 11), the environmental humidity of the high-humidity negative pressure suction is 85-99%, the negative pressure is 0.5-5 MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol.
[0088] In step 12), the high washing liquid is a mixed liquid of 50% deionized water and 50% ethanol, the washing times are 3 to 5 times, and after washing, the washing is separated by centrifugation at a speed of 3000 to 6000 rpm for 10 to 20 minutes; the temperature of the drying process is 40 to 60°C for 0.5 to 3 hours.
[0089] In step 12), the melting temperature of the twin-screw extruder is 180-320° C., the extruded nascent fibers are solidified in a water bath, and pelletized by a pelletizer.
[0090] In step 13), the drying condition is a gradient temperature increase, the first stage of temperature increase is from room temperature to 80°C over 30 minutes, the second stage of temperature increase is from 80°C to 100-120°C over 30 minutes, and the third stage of temperature increase is from 120-150°C over 1 hour.
[0091] In step 14), the polymer / high entropy carbon-based composite masterbatch obtained in 6) is loaded into the screw device A and passed into the cortex of the spinning assembly, and the high entropy vanadium-based shell phase change microcapsule composite masterbatch obtained in 13) is loaded into the screw device B and passed into the core layer of the spinning assembly. The spinning process has a temperature of 180°C to 320°C, a spinning speed of 500 to 4500 m / min, and a drafting multiple of 1 to 4 times.
[0092] The obtained double-compensation temperature-regulating fiber with a skin-core structure has a light-to-heat conversion efficiency of >2%, a phase change enthalpy value of >15 J / g, and after irradiation with a xenon arc lamp standard sunlight light source for 10 minutes, the temperature of the fabric rises by >20°C, and the temperature difference of 5°C lasts for 10 to 15 minutes.
[0093] The present invention is described in detail below in conjunction with specific embodiments, but is by no means intended to limit the present invention. Features such as preparation methods, materials, structures or composition ratios not explicitly described in this technical solution are considered to be common technical features disclosed in the prior art.
[0094] Example 1
[0095] Acetic acid, zirconium isopropoxide, hafnium isopropoxide, titanium isopropoxide, vanadium acetylacetonate and tungsten chloride were added into a mixed solvent of water and ethanol (volume ratio of 1:4) at a stoichiometric ratio of 0.02:1:0.25:0.25:0.25:0.25, and stirred at 300 r / min for 6 hours at room temperature. A mixed wet cold gas of ethanol / water below room temperature (10°C) was introduced into the solution at a gas flow rate of 100 mL / min, and a water pump was used to promote the reaction by negative pressure suction to ensure that the humidity of the reaction system was ~90% and the negative pressure was ~2 MPa. After 30 minutes of reaction, the obtained inorganic gel was transferred to a ball mill, and the mass ratio of the gel to the mass of the zirconium ball was controlled to be 1:100. The speed was 500 r / min for ball milling for 3 hours to make each inorganic source form an atomic-level mixture. The obtained uniform gel was fully dried in a vacuum oven (80°C, 3 hours) and graded calcined in a nitrogen gas atmosphere. The front stage calcination was heated to 800°C at a heating rate of 2°C / min to remove the organic side groups, and the rear stage calcination was heated to 1600°C at a heating rate of 10°C / min for rapid carbonization. Finally, the collected carbonized product was transferred to a ball mill, and the mass ratio of the carbonized product to the mass of the zirconium ball was controlled to be 1:200. The speed was 500 r / min for ball milling for 6 hours. The obtained (Ti 0.125 Hf 0.125 V 0.125 W 0.125 )Zr 0.5 C is a cubic single crystal with a particle size of 85nm. All components are evenly distributed without element segregation. Its photothermal conversion efficiency is 82%, hardness is 35GPa, and elastic modulus is 421GPa. 0.125 Hf0.125 V 0.125 W 0.125 )Zr 0.5 C nanoparticles were mixed with polyester masterbatch in a mass ratio of 1:20 and extruded and granulated by a metering twin-screw extruder. The twin-screw melting temperatures were: 260°C in zone 1, 275°C in zone 2, 290°C in zone 3, 300°C in zone 4, 305°C in zone 5, and 310°C in zone 6. The screw extrusion speed was 6 m / min. The extruded nascent fibers were solidified in tap water at 25°C, and the pelletizer speed was 6 m / min.
[0096] Polysorbate 80, deionized water and Na2HPO4·12H2O melt were added to a flask at a mass ratio of 0.1:5:20 and stirred at a speed of 500 rpm. After stirring for 5 minutes, an aqueous phase was obtained. Subsequently, n-octadecane and sorbitan oleate were added to a three-necked flask at a mass ratio of 40:1 and stirred at a speed of 500 rpm. After stirring for 8 minutes, an oil phase was obtained. The aqueous phase was added to the three-necked flask containing the oil phase, and stirred and mixed in a water bath environment. The water bath temperature was 50°C, the stirring speed was 500 rpm, and the time was 1 hour to obtain a uniformly dispersed oil-in-water emulsion. Subsequently, vanadium acetylacetonate, zirconium isopropoxide, titanium isopropoxide, thallium acetate and tungsten chloride were added into a mixed solvent of water and ethanol (volume ratio of 1:4) in a stoichiometric ratio of 1:0.25:0.25:0.25:0.25 and stirred and mixed. At room temperature, the mixture was stirred at a speed of 450 r / min for 4 hours. The mixture was then transferred to a ball mill, and the ratio of the gel mass to the zirconium ball mass was controlled to be 1:100. The mixture was ball milled at a speed of 500 r / min for 4 hours to allow the inorganic sources to form an atomic-level mixture. After the uniformly mixed sol and zirconium balls are separated, they are added to a three-necked flask containing an oil-in-water emulsion, and acetic acid is added at a ratio of one-fiftieth of the vanadium acetylacetonate dosage, and then ethanol / water mixed wet cold air below room temperature (10°C) is passed into the solution at an airflow rate of 80mL / min, and a water pump is used to promote the reaction by negative pressure suction, ensuring that the humidity of the reaction system is ~90%, and the negative pressure is ~2MPa to further hydrolyze and condense the inorganic source, forming a high-entropy vanadium-based shell at the interface of octadecane and fully encapsulating octadecane. The obtained microcapsules are washed with a washing liquid of 50% deionized water and 50% ethanol mixed liquid, and the washing times are 3 times. After washing, they are separated by centrifugation at a centrifugal speed of 6000 rpm for 10 minutes; the temperature of the drying process is 40°C and the time is 3 hours. The obtained high entropy vanadium-based shell phase change nano-microcapsules have a phase change temperature of 28°C, a phase change enthalpy value of >205 J / g, no obvious phase change hysteresis phenomenon, a stable shape of the microcapsules during the phase change process, no liquid leakage, and excellent recyclability. After 1000 heating and cooling cycles, the phase change enthalpy value retention rate is 98.2%. The obtained high entropy vanadium-based shell phase change nano-microcapsules are mixed with polyester masterbatch at a mass ratio of 1:20 and extruded and granulated by a metering twin screw. The twin screw melting temperature is: 260°C in the first zone, 275°C in the second zone, 290°C in the third zone, 300°C in the fourth zone, 305°C in the fifth zone, and 310°C in the sixth zone. The screw extrusion speed is 6m / min. The extruded primary fiber is solidified and formed in tap water at a water temperature of 25°C. The speed of the pelletizer is 6m / min.
[0097] The two mixed masterbatches were vacuum dried in a drum oven, and the drying process was that the first stage of heating was from room temperature to 80°C in 30 minutes, the second stage of heating was from 80°C to 120°C in 30 minutes, and the third stage of heating was from 1 hour to 150°C, and dried for 20 hours. The dried masterbatch was melt-spun, and the spinning process was at a temperature of 260°C to 320°C, a spinning speed of 4200 m / min, and a drafting multiple of 2.5 times. The obtained double compensation temperature regulating fiber with a skin-core structure had a light-to-heat conversion efficiency of 2.2%, a phase change enthalpy of 16.3 J / g, and a xenon arc lamp standard sunlight light source irradiation for 10 minutes, a fabric temperature rise of 22°C, and a 5°C temperature difference duration of 12 minutes.
[0098] Example 2
[0099] Hydrochloric acid, zirconium isopropoxide, thallium acetate, titanium isopropoxide, vanadium acetylacetonate and tungsten chloride were added into a mixed solvent of water and ethanol (volume ratio of 1:4) at a stoichiometric ratio of 0.02:1:0.25:0.25:0.25:0.25, and stirred at room temperature at a speed of 450 r / min for 4 hours. A mixed wet cold gas of ethanol / water below room temperature (10°C) was introduced into the solution at a gas flow rate of 80 mL / min, and a water pump was used to promote the reaction by negative pressure suction to ensure that the humidity of the reaction system was ~90% and the negative pressure was ~2 MPa. After 30 minutes of reaction, the inorganic gel was transferred to a ball mill, and the mass ratio of the gel to the mass of the zirconium ball was controlled to be 1:100. The speed was 500 r / min for 4 hours to make each inorganic source form an atomic-level mixture. The uniform gel obtained was fully dried in a vacuum oven (80°C, 3 hours) and graded calcined in a nitrogen gas atmosphere. The front stage calcination was heated to 800°C at a heating rate of 2°C / min to remove the organic side groups, and the rear stage calcination was heated to 1500°C at a heating rate of 12°C / min for rapid carbonization. Finally, the collected carbonized product was transferred to a ball mill, and the mass ratio of the carbonized product to the mass of the zirconium ball was controlled to be 1:200. The speed was 500 r / min for 6 hours. The obtained (Ti 0.125 Tl 0.125 V 0.125 W 0.125 )Zr 0.5 C is a cubic single crystal with a particle size of 120nm. All components are evenly distributed without element segregation. Its photothermal conversion efficiency is 81%, hardness is 32GPa, and elastic modulus is 409GPa. 0.125 Tl 0.125 V 0.125 W 0.125 )Zr 0.5C nanoparticles were mixed with polyester masterbatch at a mass ratio of 1:20 and extruded and granulated by a metering twin screw. The melting temperature of the twin screw was: 260°C in zone 1, 275°C in zone 2, 290°C in zone 3, 300°C in zone 4, 305°C in zone 5, and 310°C in zone 6. The screw extrusion speed was 8m / min. The extruded nascent fibers were solidified in tap water at a water temperature of 25°C. The speed of the pelletizer was 8m / min. The obtained mixed masterbatch was vacuum dried in a rotary drum oven. The drying process was that the first stage of heating was from room temperature to 80°C in 30 minutes, the second stage of heating was from 80°C to 120°C in 30 minutes, and the third stage of heating was from 1 hour to 150°C, and dried for 20 hours.
[0100] Polysorbate 80, deionized water and Na2HPO4·12H2O melt were added to a flask at a mass ratio of 0.1:5:20 and stirred at a speed of 500 rpm. After stirring for 5 minutes, an aqueous phase was obtained. Then, n-eicosane and sorbitan oleate were added to a three-necked flask at a mass ratio of 35:1 and stirred at a speed of 500 rpm. After stirring for 8 minutes, an oil phase was obtained. The aqueous phase was added to the three-necked flask containing the oil phase, and stirred and mixed in a water bath environment. The water bath temperature was 50°C, the stirring speed was 500 rpm, and the time was 1 hour to obtain a uniformly dispersed oil-in-water emulsion. Subsequently, vanadium acetylacetonate, zirconium isopropoxide, hafnium isopropoxide, thallium acetate and tungsten chloride were added into a mixed solvent of water and ethanol (volume ratio of 1:4) in a stoichiometric ratio of 1:0.25:0.25:0.25:0.25, and stirred and mixed. At room temperature, the mixture was stirred at a speed of 450 r / min for 4 hours. The mixture was then transferred to a ball mill, and the ratio of the gel mass to the zirconium ball mass was controlled to be 1:100. The mixture was ball milled at a speed of 500 r / min for 4 hours to allow the inorganic sources to form an atomic-level mixture. After the uniformly mixed sol and zirconium balls are separated, they are added to a three-necked flask containing an oil-in-water emulsion, and acetic acid is added at a ratio of one-fiftieth of the acetylacetonate vanadium stoichiometry. Subsequently, ethanol / water mixed wet cold air below room temperature (10°C) is passed into the solution at an airflow rate of 80mL / min, and a water pump is used to promote the reaction by negative pressure suction, ensuring that the humidity of the reaction system is ~90%, and the negative pressure is ~2MPa to further hydrolyze and condense the inorganic source, forming a high-entropy vanadium-based shell at the interface of eicosane and fully encapsulating octadecane. The obtained microcapsules are washed with a washing liquid of 50% deionized water and 50% ethanol mixed liquid, and the washing times are 3 times. After washing, they are centrifuged at a centrifugal speed of 6000 rpm for 10 minutes; the temperature of the drying process is 40°C and the time is 3 hours. The obtained high entropy vanadium-based shell phase change nano-microcapsules have a phase change temperature of 37°C, a phase change enthalpy value of >212 J / g, no obvious phase change hysteresis phenomenon, a stable shape of the microcapsules during the phase change process, no liquid leakage, and excellent recyclability. After 1000 heating and cooling cycles, the phase change enthalpy value retention rate is 97.5%. The obtained high entropy vanadium-based shell phase change nano-microcapsules are mixed with polyester masterbatch at a mass ratio of 1:20 and extruded and granulated by a metering twin screw. The twin screw melting temperature is: 260°C in the first zone, 275°C in the second zone, 290°C in the third zone, 300°C in the fourth zone, 305°C in the fifth zone, and 310°C in the sixth zone. The screw extrusion speed is 8m / min. The extruded primary fiber is solidified and formed in tap water at a water temperature of 25°C. The speed of the pelletizer is 8m / min.
[0101] The two mixed masterbatches were vacuum dried in a drum oven, and the drying process was that the first stage of heating was from room temperature to 80°C in 30 minutes, the second stage of heating was from 80°C to 120°C in 30 minutes, and the third stage of heating was from 1 hour to 150°C, and dried for 20 hours. The dried masterbatch was melt-spun, and the spinning process was at a temperature of 260°C to 320°C, a spinning speed of 4200 m / min, and a drafting multiple of 2.5 times. The obtained double compensation temperature regulating fiber with a skin-core structure had a light-to-heat conversion efficiency of 2.3%, a phase change enthalpy value of >15.6 J / g, and a xenon arc lamp standard sunlight light source was irradiated for 10 minutes, the fabric was heated by 25°C, and the 5°C temperature difference lasted for 11 minutes.
[0102] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A double compensation temperature regulating fiber with a skin-core structure, characterized in that: The temperature regulating fiber comprises a skin layer and a core layer; The skin layer is a photoresponsive polymer / high entropy carbon-based composite material, and the skin layer is used for photothermal conversion; The core layer is a phase-change heat storage material of a composite structure, and the core layer is used for reversible phase-change heat storage; The cortex includes a polymer matrix and high-entropy carbon-based nanoparticles, wherein the high-entropy carbon-based nanoparticles are uniformly embedded in the polymer fibers, wherein the polymer content accounts for 85-95wt% and the high-entropy carbon-based nanoparticles account for 5-15wt%; The core layer includes a polymer matrix and high entropy vanadium-based shell phase-change nano-microcapsules, wherein the nano-microcapsules are uniformly embedded in the polymer fibers, wherein the polymer content accounts for 85-95wt% and the high entropy vanadium-based shell phase-change nano-microcapsules account for 5-15wt%; In the core layer: The polymer includes one or more of polyester, polyamide, polyethylene, polypropylene, polylactic acid, and polyimide; The high entropy vanadium-based shell phase-change nano-microcapsules are composite materials with a core-shell structure; The core layer of the high entropy vanadium-based shell phase change nanocapsules is a long carbon chain aliphatic hydrocarbon phase change material, including one or more of n-octadecane, n-nonadecane, n-eicosane and n-heneicosane, with a mass ratio of 30-90wt%. The shell of the high entropy vanadium-based shell phase change nanocapsule is high entropy vanadium-based phase change material X a V b O c , wherein X is selected from four or more of Ti, Hf, Nb, Tl, Zr, and W, a is the comprehensive stoichiometric number of all elements in X, a=b, a+b=c, and the mass proportion is 10~70wt%.
2. A double compensation temperature regulating fiber with a skin-core structure according to claim 1, characterized in that: In the cortex: The polymer matrix includes one or more of polyester, polyamide, polyethylene, polypropylene, polylactic acid, and polyimide; The high entropy carbon-based nanoparticles include one or more of (Ti,Hf,Nb,Tl)ZrC, (Ti,Hf,V,Tl)ZrC, (Ti,Hf,V,Nb)ZrC, (Ti,Hf,V,W)ZrC, and (Ti,Hf,Nb,W)ZrC.
3. The double compensation temperature regulating fiber with skin-core structure according to claim 1, characterized in that: The double compensation temperature regulating fiber has a fineness of 30-300 dtex, a strength of >2.0 cN / dtex, a light-to-heat conversion efficiency of ≥2%, a phase change temperature of 20-50°C, a phase change enthalpy value of >15 J / g, and a phase change enthalpy value retention rate of >95% after 1000 heating and cooling cycles.
4. A method for preparing a double compensation temperature regulating fiber with a skin-core structure as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1: adding zirconium source, four or more inorganic precursors of Ti, Hf, Nb, Tl, Zr, W and chelating ligands to a compound solvent and uniformly mixing them, and vacuuming them under high humidity and negative pressure under stirring to obtain zirconium-based inorganic gel, and then ball milling to achieve atomic-level uniform distribution of inorganic elements to obtain uniform gel; S2: drying the uniform gel obtained in S1, and calcining it in stages under a protective gas atmosphere to obtain a single crystal high entropy carbon-based powder, and then ball milling it to obtain high entropy carbon-based nanoparticles; S3: adding the high entropy carbon-based nanoparticles obtained in S2 and the polymer masterbatch into a twin-screw extruder according to a preset mass ratio, and obtaining a uniformly mixed polymer / high entropy carbon-based composite masterbatch through high-temperature melting, extrusion molding and pelletizing processes; S4: After the polymer / high entropy carbon-based composite masterbatch and high entropy vanadium-based shell phase change nano-microcapsule composite masterbatch obtained in S3 are fully dried, they are added into two sets of feed funnels of a high-speed melt spinning machine for spinning and drawing respectively, and a spinneret assembly with a skin-core structure is used in conjunction to obtain a skin-core structured double compensation type temperature regulating fiber.
5. The method for preparing the double compensation temperature regulating fiber with skin-core structure according to claim 4, characterized in that: In S4, the preparation process of the high entropy vanadium-based shell phase change nano-microcapsule composite masterbatch includes: T1: Add polysorbate 80 to deionized water and stir thoroughly to mix evenly, melt Na2HPO4·12H2O and mix evenly with the dispersion, and obtain the aqueous phase after magnetic stirring; T2: Add long carbon chain alkane into a reaction vessel, add sorbitan oleate and stir thoroughly to obtain an oil phase; T3: adding the water phase obtained in T1 into the reaction vessel containing the oil phase in T2, heating in a water bath environment and stirring thoroughly to obtain a uniformly dispersed water-in-oil emulsion; T4: The vanadium source and four inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W are weighed in molar ratio and added into a mixed solvent for stirring, followed by ball milling to achieve uniform distribution at the atomic level; T5: slowly adding the mixed inorganic source obtained in T4 into the reaction vessel containing the water-in-oil emulsion in T3, adding the chelating ligand, and performing high-humidity negative pressure suction to further hydrolyze and condense the inorganic source, forming a high-entropy vanadium-based shell at the interface of the long carbon chain alkane and fully wrapping the core body; T6: washing the core-shell nano-microcapsules obtained in T5 with a mixed solution of ethanol and water, and fully drying to obtain high entropy vanadium-based shell phase change nano-microcapsules; T7: The high entropy vanadium-based shell phase change nano-microcapsules and polymer masterbatch obtained in T6 are added into a twin-screw extruder according to a preset mass ratio, and high entropy vanadium-based shell phase change nano-microcapsule composite masterbatch is obtained through high-temperature melting, extrusion molding and pelletizing processes.
6. The method for preparing the double compensation temperature regulating fiber with skin-core structure according to claim 5, characterized in that: In S1: The molar ratio of the zirconium source to four inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W is 1:0.25:0.25:0.25:0.25, and the molar ratio of the zirconium source to the chelating ligand is 1:0.01-0.05; The chelating ligand is acetic acid; The high humidity negative pressure suction environment humidity is 85-99%, the negative pressure is 0.5-5MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol; The ball mill is a zirconium ball dry mill with a rotation speed of 200 to 500 rpm and a time of 0.5 to 3 hours; In S2: The protective gas is high-purity nitrogen, the heating rate in the front section is controlled at 2~5℃ / min, the heating rate in the back section is controlled at 10~20℃ / min, and the holding time is 5~30min; The ball mill is zirconium ball dry milling, the rotation speed is 300-500 rpm, and the time is 3-8 hours; In S3: The melting temperature of the twin-screw extruder is 180-320° C. The extruded nascent fibers are solidified in a water bath and pelletized by a pelletizer.
7. The method for preparing the double compensation temperature regulating fiber with skin-core structure according to claim 5, characterized in that: In T1, the mass ratio of polysorbate 80, deionized water and Na2HPO4·12H2O melt is 0.1:5:20, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes; In T2, the mass ratio of the long carbon chain alkane to sorbitan oleate is 30-40:1, the stirring speed is 400-1000 rpm, and the stirring time is 1-8 minutes; In T3, the water bath temperature is 50-70°C, the stirring speed is 200-500 rpm, and the time is 0.5-3 h; In T4, the molar ratio of the vanadium source to the four inorganic precursors of Ti, Hf, Nb, Tl, Zr, and W is 1:0.25:0.25:0.25:0.25, and the ball mill is zirconium ball dry milling, with a rotation speed of 300-500 rpm and a time of 1-5 hours; In T5, the molar ratio of the vanadium source to the chelating ligand is 1:0.01-0.05; In T5, the chelating ligand is acetic acid; In T5, the environmental humidity of the high-humidity negative pressure suction is 85~99%, the negative pressure is 0.5~5MPa, and the humidity environment is constructed by a mixed liquid airflow of 50% deionized water and 50% ethanol.
8. The method for preparing the double compensation temperature regulating fiber with skin-core structure according to claim 5, characterized in that: In T6, the washing liquid used is a mixed liquid of 50% deionized water and 50% ethanol, the washing times are 3 to 5 times, and after washing, the centrifugal separation is performed at a centrifugal speed of 3000 to 6000 rpm for 10 to 20 minutes, and the drying temperature is 40 to 60°C for 0.5 to 3 hours; In T7, the melting temperature of the twin-screw extruder is 180-320° C., the screw speed is 5-50 m / min, the extruded nascent fibers are solidified in a water bath, and the pelletizer speed matches the screw speed.
9. The method for preparing the double compensation temperature regulating fiber with skin-core structure according to claim 4, characterized in that: In S4, the drying condition is a gradient temperature increase, the first stage of temperature increase is from room temperature to 80°C over 30 minutes, the second stage of temperature increase is from 80°C to 100-120°C over 30 minutes, and the third stage of temperature increase is from 120-150°C over 1 hour; In S4, the polymer / high entropy carbon-based composite masterbatch is loaded into the screw device A and passed into the cortex of the spinning assembly, and the high entropy vanadium-based shell phase change microcapsule composite masterbatch is loaded into the screw device B and passed into the core layer of the spinning assembly. The spinning process has a temperature of 180°C to 320°C, a spinning speed of 500 to 4500 m / min, and a drafting multiple of 1 to 4 times.
Citation Information
Patent Citations
Preparation method of skin-core type photothermal conversion-heat storage temperature regulation polyester fiber
CN115341302A
Heat-generating phase-change core-sheath fiber and preparation method thereof
CN107587207A
(HfTaZrTiNb) C high-entropy ceramic powder and preparation methods of high-entropy ceramic powder and high-entropy ceramic blocks
CN108439986A